Cutaneous apocrine adenocarcinoma in a goat - Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2023)
Apocrine neoplasms are rare in goats. This report describes an apocrine adenocarcinoma in a 5-year-old female Boer goat with an ulcerated, exophytic, multilobulated mass on the left dorsolateral cervical area. Histologically, the dermis was effaced and expanded by a poorly demarcated epithelial neoplasm with desmoplasia. Neoplastic cells were arranged in acini with papillary projections into the lumen and had cuboidal or columnar, eosinophilic, occasionally vacuolated cytoplasm. Nuclei were round and had finely stippled chromatin with one nucleolus. Neoplastic cells contained periodic acid-Schiff (PAS)–positive and diastase– resistant, alcian blue–positive cytoplasmic granules. There were 6 mitoses in 2.37 mm2 (equivalent to 10 FN22/40X fields). Histologic and histochemical features in the current case were consistent with a cutaneous apocrine gland adenocarcinoma.